2021
DOI: 10.1111/eea.13125
|View full text |Cite
|
Sign up to set email alerts
|

Aphis spiraecola and Aphis (Toxoptera) citricidus differently manipulate plant metabolism to gain fitness in terms of population abundance or dispersal

Abstract: The response of plant cultivars to infestation by single aphid species has been widely reported, whereas the response of plants to multiple aphid species, and the mechanisms by which various aphids benefit from the induced changes, has been largely ignored. Here we analyzed the symptoms and physiological responses of sweet orange, Citrus sinensis (L.) Osbeck (Rutaceae), as affected by Aphis spiraecola Patch and Aphis (Toxoptera) citricidus (Kirkaldy) (Hemiptera: Aphididae). We further compared the feeding beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…For individual aphid infestation, Aphis spiraecola only enhanced the expression of one SA marker gene, whereas Aphis citricidus only decreased the expression of one JA marker gene. In a previous study, however, we showed that Aphis spiraecola significantly activated several SA and JA marker genes of host plant, while Aphis citricidus induced SA marker genes but repressed JA marker genes expression 15 . The difference in methodology (time interval between aphid removal and leaf sample collection) between these two studies may explain these different results.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…For individual aphid infestation, Aphis spiraecola only enhanced the expression of one SA marker gene, whereas Aphis citricidus only decreased the expression of one JA marker gene. In a previous study, however, we showed that Aphis spiraecola significantly activated several SA and JA marker genes of host plant, while Aphis citricidus induced SA marker genes but repressed JA marker genes expression 15 . The difference in methodology (time interval between aphid removal and leaf sample collection) between these two studies may explain these different results.…”
Section: Discussionmentioning
confidence: 64%
“…The polyphagous spirea aphid, Aphis spiraecola Patch and oligophagous brown citrus aphid, Aphis ( Toxoptera ) citricidus (Kirkaldy) are two common citrus aphid species in citrus orchards, and they occur sympatrically with Diaphorina citri in many regions 14 . During an earlier investigation, we found that Aphis spiraecola and Aphis citricidus differentially induced physiological and defense responses of host plant after 2 days of infestation 15 . We speculate such difference may subsequently induce different plant‐mediated effects on Diaphorina citri .…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Similar to D. citri , many citrus aphids preferentially feed and develop on young shoots and leaves. We previously reported that the citrus aphids Aphis spiraecola Patch and Aphis ( Toxoptera ) citricidus (Kirkaldy) manipulated citrus phytohormone-dependent defenses in different ways [ 25 ] and also that A. spiraecola and A. citricidus decrease and increase D. citri reproduction and feeding, respectively [ 26 ].…”
Section: Introductionmentioning
confidence: 99%